Introducing Book Networks and Cultural Capital: Space, Society and the Nation - Howsam, Leslie (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherche et d’étude sur le livre au Québec, 2010)
The opening article,“Introducing Book Networks and Cultural Capital: Space, Society & the Nation,” has two purposes. The first is to explicate the theme of this third issue of Mémoires du Livre/Studies in Print Culture, co-edited by Leslie Howsam and Jane McLeod. That theme emerges from a conference where several of the papers originated, a meeting of the Canadian Association for the Study of Book Culture/Association canadienne pour l’étude de l’histoire du livre, held in 2009 in Ottawa at the Congress of the Humanities and Social Sciences. The second purpose is to contextualize and provide brief introductions to the eight articles, linking them in a tripartite analysis of networks – face-to-face societies, imagined communities where reading creates or reinforces identities, and the anachronistic networks that emerge when books are re-read and re-interpreted across a span of decades, or even centuries.